Audit Committee’s Roles & Effectiveness: Evidence from Indonesia - Sudjono, Andrew Christian; Setiawan, Amelia (Faculty of Economics, Universitas Sriwijaya, 2024)
Financial statement manipulation that still occurring nowadays in Indonesia leads the following issue of how audit committee’s functioning within a corporation. This study questions whether audit committee has certain significant role as stated by OJK or just a formality to obey the regulation set by the government. Therefore, this research analyzes the audit committees’ effectiveness in Indonesia by using POJK No. 55/POJK.04/2015 as the basis of measurement. To examine the audit committee’s effectiveness, this research gathers primary data by distributing a questionnaire to audit committee’s in listed companies in Indonesia and to Ikatan Komite Audit Indonesia (IKAI). Based on the responses, the data is then analyzed by using the SEM-PLS approach. It is found that audit committee diligence in audit and decision-making areas significantly increases the audit committee activity. Moreover, audit committee activity and responsibility in internal audit, regulatory compliance, and risk management significantly influence the audit committee’s effectiveness.